Conservation and management implications of genetic and geometric scale variation in the ancient fish giant featherback ( Chitala lopis ) - Boby Muslimin; Gunawan Muhammad; Arif Wibowo; Kurniawan Kurniawan; Vitas Atmadi Prakoso; Rendy Ginanjar; Mochammad Zamroni; Bayu Kreshna Adhitya Sumarto; Septiana Sri Astuti; Deni Irawan; Agus Priyadi; Mirna Dwirastina; et al. (Journal of Fish Biology, 2026)
Giant featherback ( Chitala lopis ) is an ancient species of freshwater fish considered globally extinct until extant populations were re‐discovered in the Sundaland region of Indonesia in 2022. To improve management of the remaining populations, this study used genomic DNA and landmark‐based geometric morphometric analyses of fish scales to evaluate whether these approaches can discriminate among phylogenetic clades, sexes and broad habitat ecotypes inhabited by extant C. lopis populations. DNA analyses of 39 specimens from eight rivers provided the first evidence of two phylogenetic clades: (i) those from Central and South Borneo and (ii) those from West Borneo, Riau, South Sumatra and Jambi. Scale morphology was characterised across eight body areas using scale dimensions (relative height and width to standard length and height‐to‐width ratio), centroid size and Procrustes shape coordinates, with repeated‐measures structure accounted for using linear mixed models and Procrustes ANOVA with a randomised residual permutation procedure (RRPP). Scale dimensions and centroid size varied significantly among body areas (all p p = 0.024), with Clade 2 individuals consistently showing lower values than Clade 1, though scale geometry overall showed limited promise as a rapid non‐destructive stock discriminator. Both clade and sex had small but significant effects on Procrustes scale shape ( R 2 = 0.015 and 0.013, respectively; both p = 0.001), while phenotypic trajectory analysis revealed that males exhibited a significantly greater amplitude of scale shape change across body positions than females (trajectory magnitude: M = 0.289, F = 0.207; p = 0.034), despite both sexes following parallel shape trajectories along the body axis. These results provide a novel morphometric baseline for C. lopis and highlight the importance of body‐position‐specific and multivariate approaches when characterising scale morphology in endangered freshwater fishes.

Reframing Fish Passage Prioritization for Human Nutrition Outcomes - Nicolette Duncan; Ana Horta; John Conallin; Tim Marsden; Abigail J. Lynch; Ivor Stuart (Environmental Management, 2025)
Water control infrastructure forms barriers that fragment river habitats, reducing aquatic biodiversity and the ecosystem services it provides. Irrigation infrastructure, for example, although implemented to support food production, highlights problematic trade-offs against wild food systems like inland fisheries which are a critical food resource for tens of millions of people, particularly in tropical countries. To reduce fragmentation at a broad range of barriers, fish passage technology is sometimes implemented to support migrating fish, aided by frameworks designed to prioritize barriers for remediation. This study critically evaluated 93 fish passage barrier prioritization frameworks globally to explore how they could strategically guide fish passage investments in tropical contexts and identify criteria relevant to delivering on nutrition security outcomes. Results showed prioritization frameworks were ill-equipped to support the broader human development goals that may drive fish passage investments in tropical countries, such as supporting human nutrition under United Nations Sustainable Development Goal (SDG) 2: Zero Hunger. Tropical contexts were underrepresented despite substantial recent fish passage investment, whereas temperate and conservation focused frameworks, particularly from North America, dominated. These findings prompt reflection on the inherent biases in fish passage barrier prioritization frameworks and criteria. Improving understanding of and collaboration with local partners to integrate SDG 2 into future prioritization frameworks could improve fish passage infrastructure and help support better nutrition and food production for communities.

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

More than the sum of their parts — Environmental flows increase fish movement and fishway functionality - Matthew Jones; Paul Moloney; Robin Hale; Ivor Stuart; Justin O'Connor; Zeb Tonkin (Ecological Engineering, 2025)

Characterizing spatial patterns among freshwater fishes and shrimps of the Poso River (Sulawesi, Indonesia) using DNA barcoding - Arif Wibowo; Kurniawan Kurniawan; Vitas Atmadi Prakoso; Rendy Ginanjar; Fathur Rochman; Mochammad Zamroni; Dwi Atminarso; Bayu Kreshna Adhitya Sumarto; Andi Chadijah; Deni Irawan; Tri Deniansen; Irma Suriani; et al. (Aquatic Sciences, 2025)
Fish biodiversity assessments are vital for understanding threats and aquatic ecosystem health. In the Poso River, Central Sulawesi, changes in biodiversity are influenced by habitat alteration, non-native species, and overfishing. This study evaluates fish and crustacean biodiversity in the Poso River system to address these challenges for improving fisheries management, conservation, and fish passage integration into hydropower development. The present biodiversity study utilized a comprehensive methodology that encompassed both traditional taxonomic approaches and DNA barcoding, specifically targeting the mitochondrial cytochrome c oxidase subunit-1 ( COI ) gene for accurate species identification and spatial boundary validation. The survey was conducted in the upstream, hydropower area and downstream areas of the river. We found 27 species of fish in the Poso River, including both native (e.g., Anguilla celebesensis , Oryzias nebulosus , Rhyacichthys aspro ) and non-native species (e.g., Melanochromis auratus , Amphilophus trimaculatus , Oreochromis niloticus ). Two International Union for Conservation of Nature (IUCN) red listed endangered species were also observed (e.g., Adrianichthys poptae and Mugilogobius sarasinorum ). DNA barcoding was performed to examine species spatial boundaries. The fish population in the Poso River was dominated by non-native species, accounting for 85.70% of the total population. The upstream reaches had the highest fish abundance and diversity, while the downstream reaches had the lowest. There was, however, no significant difference in species richness and diversity across different locations and seasons. The dominance of non-native species in the Poso River necessitates the improvement of existing fishways within the hydropower dams potentially through the development of selective technology that can block the distribution of these non-native species. This research highlights the critical issue of non-native species proliferation and the potential threat they pose to native fish populations, providing valuable insights for conservation and management efforts in Indonesia and similar ecosystems worldwide.

Large-scale serial replacement of invasive tench (Tinca tinca) by invasive carp (Cyprinus carpio) in the presence of redfin perch (Perca fluviatilis) in the Murray-Darling River system, Australia - Matthew P. Hill; Peter Caley; Ivor Stuart; Richard P. Duncan; David M. Forsyth (Biological Invasions, 2024)
Ecosystems worldwide are increasingly being invaded by multiple species, and the rate of biological invasion is accelerating, leading to more interactions among invasive species. One such interaction that has received little attention is the phenomenon of ‘serial replacement’ or ‘over-invasion’, where an established invasive species is supplanted by a second invasive species. Understanding this interaction is important as controlling the second species could inadvertently lead to an increase in the abundance of the first species. We used a hierarchical state-space model to analyse changes in annual abundances (commercial catch-per-unit-effort) of three invasive fish species, tench ( Tinca tinca ), common carp ( Cyprinus carpio ) and redfin perch ( Perca fluviatilis ), in the Murray-Darling River system (MDRS), Australia between 1954–2002. Tench were present at low abundances until the mid-1970 s, before declining to the point of no commercial catch post-1989. This rapid decline coincided with a significant increase in carp abundance, suggesting that carp may have driven the tench decline through habitat modification (particularly the destruction of aquatic plants), consistent with findings from European studies that show the disappearance of tench from ponds with intensive carp farming. Redfin perch populations, were inferred to be much less impacted by the invading carp population. While carp were present in the MDRS for the duration of the study, the rapid increase in carp abundance in the early 1970 s coincided with the introduction of a specific genetic lineage—the “Boolarra strain”. Our analysis provides compelling evidence of serial replacement of long-established tench by invading common carp triggered by the introduction of a novel carp strain.

Rock fishways: Natural designs for an engineered world - Ivor G. Stuart; Timothy J. Marsden; Matthew J. Jones; Matt T. Moore; Lee J. Baumgartner (Ecological Engineering, 2024)

Factors influencing migration of short‐finned eels ( Anguilla australis ) over 3 years from a wetland system, Lake Condah, south‐east Australia, downstream to the sea - Wayne Koster; Ben Church; David Crook; David Dawson; Ben Fanson; Justin O'Connor; Ivor Stuart (Journal of Fish Biology, 2024)
Anguillid eel populations are under threat globally. A particularly vulnerable life‐cycle stage is the migration of mature adult eels downstream from freshwater habitats through estuaries into the sea to spawn. This study investigated the factors associated with downstream migration of the short‐finned eel Anguilla australis (Richardson 1841) from a coastal wetland (Lake Condah) in south‐east Australia, using acoustic telemetry. Migration was associated with time of the year, higher water level and river flows, decreasing water temperature, and darker moon phases. Larger individuals and those in better condition were more likely to migrate from the wetland. Downstream migration peaked in spring, in contrast to the typical autumn migration period for other temperate anguillids. Variable responses, in comparison to other studies, highlight how migration cues may not be universal. In south‐east Australia, short‐finned eels may have evolved to migrate in multiple phases by first migrating to the estuary during typical seasonal spring flow pulses (e.g., to avoid being stranded in upland reaches during dry summer periods) and then migrating into the ocean in autumn. More research is needed to unravel these processes and causes, especially considering that the relationship between migration and hydrology may be complex and confounded (e.g., by human‐induced disruptions to migratory pathways).

Modelling the response of common carp (Cyprinus carpio) to natural and managed flows using a stochastic population model - Charles R. Todd; John D. Koehn; Ivor G. Stuart; Henry F. Wootton; Brenton P. Zampatti; Leigh Thwaites; Anthony Conallin; Qifeng Ye; Kasey Stamation; Chris Bice (Biological Invasions, 2024)

Swinging back from the brink? Polygamous mating strategies revealed for an iconic threatened freshwater fish - Elise M. Furlan; Lee J. Baumgartner; Meaghan Duncan; Iain Ellis; Bernd Gruber; Katherine Harrisson; Laura Michie; Jason D. Thiem; Ivor Stuart (Science of The Total Environment, 2024)

Assessing impacts of a notorious invader (common carp Cyprinus carpio) on Australia's aquatic ecosystems: Coupling abundance-impact relationships with a spatial biomass model - Benjamin G. Fanson; Robin Hale; Jason D. Thiem; Jarod P. Lyon; John D. Koehn; Andrew F. Bennett; Ivor Stuart (Biological Conservation, 2024)

Elevated river discharge enhances the immigration of juvenile catadromous and amphidromous fishes into temperate coastal rivers - Frank Amtstaetter; Jian D.L. Yen; Robin Hale; Wayne Koster; Justin O'Connor; Ivor Stuart; Zeb Tonkin (Journal of Fish Biology, 2021)
Anthropogenic alterations to river flow regimes threaten freshwater biodiversity globally, with potentially disproportionate impacts on species that rely on flow cues to trigger critical life history processes, such as migration for diadromous fishes. This study investigates the influence of river discharge on the abundance of juvenile fish moving into rivers by four temperate catadromous or amphidromous species (common galaxias Galaxias maculatus , spotted galaxias Galaxias truttaceus , climbing galaxias Galaxias brevipinnis and the threatened Australian grayling Prototroctes maraena ). Fyke netting or fishway trapping was used to catch juvenile fish moving from estuaries into freshwater in five coastal waterways in south‐eastern Australia during the spring migratory period. There was a positive relationship between the probability of high catch rates and mean discharge in September. We also found a positive relationship between discharge and the number of recruits captured 22–30 days later in a flow stressed system. In addition, day‐of‐year had a strong influence on catch rates, with the peak abundance of juveniles for three species most likely to occur midway through the sampling period (spotted galaxias in October, climbing galaxias in late October and Australian grayling in late October and early November). Our study shows that higher magnitudes of river discharge were associated with increased catches of juvenile catadromous and amphidromous fishes. With a limited supply of environmental water, environmental flows used to enhance immigration of these fishes may be best targeted to maintain small amounts of immigration into freshwater populations in waterways or years when discharges are low and stable. When there are natural, large discharge volumes, relatively large numbers of juvenile fish can be expected to enter coastal waterways and during these times environmental flows may not be required to promote immigration.

Fish‐Net: Probabilistic models for fishway planning, design and monitoring to support environmentally sustainable hydropower - Martin Wilkes; Lee Baumgartner; Craig Boys; Luiz G M Silva; Justin O'Connor; Matthew Jones; Ivor Stuart; Evelyn Habit; Oscar Link; J Angus Webb (Fish and Fisheries, 2018)
The construction of fishways for upstream and downstream connectivity is the preferred mitigation measure for hydropower dams and other riverine barriers. Yet empirical evidence for effective design criteria for many species is missing. We therefore assembled a group of international fishway designers and combined their knowledge with available empirical data using a formal expert elicitation protocol and Bayesian networks. The expert elicitation method we use minimizes biases typically associated with such approaches. Demonstrating our application with a case‐study on the temperate Southern Hemisphere, we use the resulting probabilistic models to predict the following, given alternative design parameters: (i) the effectiveness of technical fishways for upstream movement of migratory fish; (ii) habitat quality in nature‐like bypasses for resident fish; and (iii) rates of mortality during downstream passage of all fish through turbines and spillways. The Fish Passage Network (Fish‐Net) predicts that fishways for native species could be near 0% or near 100% efficient depending on their design, suggesting great scope for adequate mitigation. Sensitivity analyses revealed the most important parameters as follows: (i) design of attraction and entrance features of technical fishways for upstream migration; (ii) habitat preferences of resident fish in nature‐like bypasses; and (iii) susceptibility of fish to barotrauma and blade strike during turbine passage. Numerical modelling predicted that mortality rates of small‐bodied fish (50–100 mm TL ) due to blade strike may be higher for Kaplan than Francis turbines. Our findings can be used to support environmentally sustainable decisions in the planning, design and monitoring stages of hydropower development.

Using a Population Model to Inform the Management of River Flows and Invasive Carp (Cyprinus carpio) - John D. Koehn; Charles R. Todd; Brenton P. Zampatti; Ivor G. Stuart; Anthony Conallin; Leigh Thwaites; Qifeng Ye (Environmental Management, 2018)

Make the Most of the Data You’ve Got: Bayesian Models and a Surrogate Species Approach to Assessing Benefits of Upstream Migration Flows for the Endangered Australian Grayling - J. Angus Webb; Wayne M. Koster; Ivor G. Stuart; Paul Reich; Michael J. Stewardson (Environmental Management, 2018)

Population dynamics of invading freshwater fish: common carp (Cyprinus carpio) in the Murray-Darling Basin, Australia - David M. Forsyth; John D. Koehn; Darryl I. MacKenzie; Ivor G. Stuart (Biological Invasions, 2013)

The use of sectioned otoliths to age barramundi (Lates calcarifer) (Bloch, 1790) [Centropomidae] - Ivor G. Stuart; Stephen C. McKillup (Hydrobiologia, 2002)